2020
DOI: 10.1097/jxx.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Debate as a learning tool in an online environment

Abstract: Debate offers an opportunity to increase student interaction and develop critical thinking and presentation skills. The investigators used an online debate during a first-semester Doctor of Nursing Practice (DNP) course. The purpose of this evaluation was to 1) evaluate the feasibility of conducting a live-streamed debate and 2) assess students' perceived gained skills. Student pairs were assigned to speak for or against a statement applicable to professional practice of a DNP-prepared nurse approximately 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Open-ended survey responses revealed positive student perceptions of the experience, despite initial anxiety and nervousness about their perceived ability to present and defend a professional issue. These findings align with the work of DeClerk and colleagues, 2 who found that, although students expressed uncertainty about what to expect in debates, it led students to critically examine and apply the literature on their topic and present their view. Students faced typical barriers to assignment completion that are associated with online and group work formats.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Open-ended survey responses revealed positive student perceptions of the experience, despite initial anxiety and nervousness about their perceived ability to present and defend a professional issue. These findings align with the work of DeClerk and colleagues, 2 who found that, although students expressed uncertainty about what to expect in debates, it led students to critically examine and apply the literature on their topic and present their view. Students faced typical barriers to assignment completion that are associated with online and group work formats.…”
Section: Discussionsupporting
confidence: 87%
“…1 Through debates, students interact actively with their classmates, with the topic, and with the instructor. 1,2 Students learn important skills through debates, including critical thinking, working effectively with others, leadership, delegation, communication skills, and how toevaluate team members. 1 Graduate nursing students' perception of participating in an online debate included the themes of risk taking, defense of a position, coverage of all aspects of the topic, skill and knowledge transfer, and critical thinking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Online Platforms: Although not employed here, the classic debate structure lends itself well to the online environment either synchronously via video conferencing ( DeClerk, LaBorde and Smith-Olinde, 2020 ) or asynchronously via forums ( Lin and Crawford, 2007 ). This flexibility is a crucial feature considering the challenges posed by the COVID-19 pandemic on traditional teaching strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Instructors can hold synchronous meetings where students engage in a real-time debate on a predetermined topic (Cheese, 2015;DeClerk et al, 2020). For instance, students could be split into different groups where they must argue either for or against something.…”
Section: Debatesmentioning
confidence: 99%